Method for Determining the Contribution of Fluorescence to an Optical Signature, with Implications for Postulating a Visual Function - Mazel, Charles (Frontiers in Marine Science, 2017)
The fluorescence of many marine organisms is a visually compelling phenomenon. Descriptions of the phenomenon have at times been accompanied by suggestions of a visual function, but with minimal supporting evidence. It is possible to make quantitative estimates of the contribution of fluorescence emission to a visual signal under arbitrary illumination conditions. This analysis can help in deciding whether further research into a visual function is warranted, or whether the fluorescence is an interesting epiphenomenon associated with biomaterials that are present for other purposes. This paper describes the concepts associated with visual signals consisting of both reflected and fluoresced light, and methods for determining the underlying optical properties and using that information to model visual signal under environmentally relevant illumination conditions.